2023
DOI: 10.7225/toms.v12.n01.w01
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Dry Ports into the National Transport Policy: A Proposal for International Trade Acceleration

Abstract: The Malaysian National Transport Policy (NTP) aims to develop a conducive ecosystem for the transport sector, facilitate seamless cargo movement, promote public mobility, enhance public transport competitiveness, and build an intelligent and green transport system. However, the policy does not comprehensively cover the lack of assimilation of inland components with the seaport system. To close the gaps, this paper thoroughly discusses the three main objectives proposed for the study: first, to understand the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Dry port research has predominantly focused on various distinct topical areas, discussing the definitions, functions, policy and governance, ownership, dry port-seaport interaction, dry port performance, dry port location, and multimodal transportation [24,28,71]. Researchers do acknowledge that issues such as sustainable dry port operations, internal dry port sustainability, trade supply chain networks, stakeholder collaboration, and service quality have not been thoroughly researched nor given priority [46]. Nonetheless, these issues play a significant role in ensuring dry port sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry port research has predominantly focused on various distinct topical areas, discussing the definitions, functions, policy and governance, ownership, dry port-seaport interaction, dry port performance, dry port location, and multimodal transportation [24,28,71]. Researchers do acknowledge that issues such as sustainable dry port operations, internal dry port sustainability, trade supply chain networks, stakeholder collaboration, and service quality have not been thoroughly researched nor given priority [46]. Nonetheless, these issues play a significant role in ensuring dry port sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the field of study is still developing and fragmented, five key theme areas have been identified: concept development, environmental effects, economic effects, performance of dry ports, and network effects [12]. Jeevan et al [46] indicated that the dry port research has focused on six thematic areas: port governance and policy, port management, performance and competition, planning and development, dry port operation, and spatial analysis. Therefore, acquiring a comprehensive understanding of the existing literature through bibliometric analysis is important to track research developments in dry port sustainability, identify research gaps to serve as a springboard for subsequent studies, and mitigate disparities in defining thematic areas of studies in dry port sustainability.…”
Section: Sustainable Development Goalmentioning
confidence: 99%
“…However, the primary task of a seaport is to provide shelter and support services for ships, handle cargo and passengers, link various modes of transport, and function as a base for industrial development (Jeevan et al, 2021a;Salleh et al, 2023). Driving factors of seaport development over the years include economic, technological, and political factors as well as the logistics integration between the foreland hinterlands (Rodrigue & Notteboom, 2000;Robinson, 2002;Jeevan et al, 2021b;Jeevan et al, 2023). The anyport model indicates that a seaport mostly depends on geographical factors (Notteboom, 2000).…”
Section: Seaport Life Cyclementioning
confidence: 99%